CD8 T cell response and its released cytokine IFN-γ are necessary for lung alveolar epithelial repair during bacterial pneumonia - Zhang, Xiaoying; Ali, Mir; Pantuck, Morgan Alexandra; Yang, Xiaofeng; Lin, Chih-Ru; Bahmed, Karim; Kosmider, Beata; Tian, Ying (Frontiers in Immunology, 2023)
Introduction Alveolar epithelial regeneration depends on the activity of resident quiescent progenitor cells. Alveolar epithelial type II (AT2) cells are known as the alveolar epithelial progenitor cells. They exit quiescent state, proliferate rapidly in response to injury and differentiate into alveolar epithelial type I (AT1) cells to regenerate the damaged alveolar epithelium. Although AT2 cell plasticity has been a very intense field of research, the role of CD8 T cell response and their released cytokine IFN-γ, in regulating AT2 cell plasticity and alveolar epithelial repair and regeneration after injury remains largely unknown. Methods We used flow cytometry to quantify the amount of CD8 T cells in mouse lungs after bacterial pneumonia caused by Streptococcus pneumoniae. To determine whether CD8 T cells and their released cytokine IFN-γ are necessary for AT2 cell activity during alveolar epithelial regeneration, we performed loss of function studies using anti-CD8 or anti-IFN-γ monoclonal antibody (mAb) treatment in vivo. We assessed the effects of CD8 T cells and cytokine IFN-γ on AT2 cell differentiation capacity using the AT2- CD8 T cell co-culture system in vitro. Results We detected a transient wave of accumulation of CD8 T cells in mouse lungs, which coincided with the burst of AT2 cell proliferation during alveolar epithelial repair and regeneration in mice following bacterial pneumonia caused by Streptococcus pneumoniae. Depletion of CD8 T cells or neutralization of cytokine IFN-γ using anti-CD8 or anti-IFN-γ monoclonal antibody significantly reduced AT2 cell proliferation and differentiation into AT1 cells in mice after bacterial pneumonia. Furthermore, co-culture of CD8 T cells or cytokine IFN-γ with AT2 cells promoted AT2-to-AT1 cell differentiation in both murine and human systems. Conversely, blockade of IFN-γ signaling abrogated the increase in AT2-to-AT1 cell differentiation in the AT2- CD8 T cell co-culture system. Discussion Our data demonstrate that CD8 T-cell response and cytokine IFN-γ are necessary for promoting AT2 cell activity during alveolar epithelial repair and regeneration after acute lung injury caused by bacterial pneumonia.